Interposed Crimes and Pakistan: Causes and Consequences - Zeenat; Butt, Ibtasam Zafar; Malik, Ayesha (Journal of Development and Social Sciences, 2024)
The objective of this study is to explore the influence of interposed crime on Pakistan’s national security and socioeconomic stability. This study also observes non-traditional security risks associated with transnational crimes, such as the effects on the environment, economy, society, and health. Transnational crime refers to criminal organizations that function across national borders. This encompasses criminal organizations that traffic in a variety of goods, including people, weapons, drugs, mining, and other items. Due to its geographical location, Pakistan faces security issues after her independence and still today. The methodology used in this research is primarily qualitative method, and also uses of historical, exploratory, and descriptive approach used to define the impacts of interposed crime on Pakistan. The finding of this study existing legal framework and their policies would not be implemented properly. Political instability and economic inequality creates hurdles to combat interposed crime in Pakistan .This study recommends that implementation of laws well managed policies, training, educational initiatives, raising public awareness , economic equality ,socio-political stability , strong governance and international cooperation is necessary for reducing the effects of interposed crime on Pakistan non- traditional security.